Seminar Kewirausahaan Posko 7 MIT-19 KKN UIN Walisongo: Strategi Branding Digital Untuk UMKM di Desa Bedono - Hava Haniva Ariantara; Meidina Putri; Imanu Massu Barlinti; Malika Latifah Salma; Salsabila Ilmi Rizqika; Baroroh Sofiati; Putri Rahmawati; Alisa Dewi Rahmawati; Tiara Nabilazen; Haris Mayudaee; Meika Puji Andini; Ghilman Kharizi; Yazid Munawwir; Safrida Khoirun Nisa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The Entrepreneurship Seminar held by Post 7 MiT-19 KKN UIN Walisongo in Bedono Village is part of the community empowerment program, especially in supporting the progress of Micro, Small, and Medium Enterprises (MSMEs). This activity raised the theme